Barriers to the use of kangaroo mother care in mothers of low-birth-weight infants in Madagascar - Ranosiarisoa, Zoly N.; Ramanarivo, Mihary S. K.; Mongarçon, Ahamadi; Razafimanantsoa, Harinirina A.; Andriatahina, Todisoa N.; Robinson, Annick L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Worldwide, complications of preterm birth and low birth weight are the leading cause of death among newborns and so were in Madagascar. Kangaroo mother care (KMC) is an essential neonatal health intervention to reduce mortality and morbidity in preterm infants. Despite this, mothers face several obstacles in its daily practice. The objective of our study was to identify the barriers that oppose mother’s adherence to KMC in order to seek solutions. Methods: This was a descriptive cross-sectional study including low birth weight infants whose parents have refused or abandoned the practice of KMC. We conducted an interview either face-to-face or by phone call with open-ended and then semi- structured questions. Results: Among 444 low birth weight (LBW) newborns who should be admitted to the kangaroo unit: fifty-seven (12%) did not receive or abandoned KMC during hospitalization. Fourteen infants whose mothers answered the phone call no longer returned to outpatient follow-up. We retained 71 infants whose mothers did not fully adhere to the KMC stages. Financial barriers were the main obstacles, especially transport costs n=47 (66.2%); then parental and family barriers, in particular family organization in relation to household chores n=26 (36.7%); including hospital barriers especially geographical distance from the hospital n=25 (35.2%). Conclusions: To improve mothers’ access and promote the health of premature infants, social assistance: such as transport support, provision of medical insurance, meals, home visits and intervention of psychologists are necessary.